Potential impact of biocide adaptation on selection of antibiotic resistance in bacterial isolates - Engy Elekhnawy; Fatma Sonbol; Ahmed Abdelaziz; Tarek Elbanna (SpringerOpen, 2020)
Abstract Background Antibiotic resistance in pathogenic bacterial isolates has increased worldwide leading to treatment failures. Main body Many concerns are being raised about the usage of biocidal products (including disinfectants, antiseptics, and preservatives) as a vital factor that contributes to the risk of development of antimicrobial resistance which has many environmental and economic impacts. Conclusion Consequently, it is important to recognize the different types of currently used biocides, their mechanisms of action, and their potential impact to develop cross-resistance and co-resistance to various antibiotics. The use of biocides in medical or industrial purposes should be monitored and regulated. In addition, new agents with biocidal activity should be investigated from new sources like phytochemicals in order to decrease the emergence of resistance among bacterial isolates.